2019
DOI: 10.3390/v11040308
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Evolutionary Analyses of Carnivore Protoparvovirus 1 NS1 Gene

Abstract: Carnivore protoparvovirus 1 is the etiological agent of a severe disease of terrestrial carnivores. This unique specie encompasses canine parvovirus type 2 (CPV-2) and feline panleukopenia virus (FPLV). Studies widely analyzed the main capsid protein (VP2), but limited information is available on the nonstructural genes (NS1/NS2). This paper analyzed the NS1 gene sequence of FPLV and CPV strains collected in Italy in 2009–2017, along with worldwide related sequences. Differently from VP2, only one NS1 amino-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 72 publications
6
43
1
Order By: Relevance
“…Moreover, the evidence in the NS1/NS2 gene sequences of amino acid mutations with respect to the other CPV strains spreading worldwide (NS1: 60V, 544F, 545F, 630P ‐ NS2: 60V, 151N, 152V) could contribute to further elucidate its evolution (Mira et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the evidence in the NS1/NS2 gene sequences of amino acid mutations with respect to the other CPV strains spreading worldwide (NS1: 60V, 544F, 545F, 630P ‐ NS2: 60V, 151N, 152V) could contribute to further elucidate its evolution (Mira et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing encompassing both ORFs (NS and VP genes) was carried out using primer pairs developed by Pérez et al (), as previously described (Mira et al, ). Sequences were assembled according to an overlapping strategy and analysed using BioEdit ver 7.0.5.3 software (Hall, ).…”
Section: Methodsmentioning
confidence: 99%
“…Limited studies are available on the CPV non‐structural genes (Hoelzer et al, ; Pérez et al, ), and, only recently, the analysis of the NS1 gene sequence was included in the CPV phylogenies from several countries (Canuti, Rodrigues, Whitney, & Lang, ; Grecco et al, ; Mira, Canuti, et al, ; Mira, Purpari, et al, ; Zhuang et al, ). In this study, sequence analysis revealed aa changes previously described mainly in NS1/NS2 gene sequences of CPV‐2a/2c strains of Asian origin.…”
Section: Discussionmentioning
confidence: 99%
“…This divergence may suggest the same ancestral origin with the CPV strains of Asian origin but a separate evolution, as well as a continuous adaptive process of the virus in separate environments. Indeed, some of these changes lay in the potential encoding sequence of functional domains (Mira, Canuti, et al, ) and, particularly, residues 351, 517 and 545 are located between the α5‐ and α6‐helices, between the β5‐ and α11‐helices and just close to the α11‐helix of the helicase domain protein sequence, respectively, as illustrated in Niskanen, Ihalainen, Kalliolinna, Häkkinen, and Vihinen‐Ranta (). Therefore, their role needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation